Incidence of Some Pathogenic Organisms in Cultured Shrimp (Penaeus monodon) Collected from Chilaw - Fonseka, T.D.G.; Hettiarachchi, K. (My University, 1991)
Samples offarm shrimp and pond water were collectedfrom Chi/aw. Total bacterial counts of coliforms and Escherichia coli are reportedfor these samples. Pathogens Vibrio parahaemolyticus, and Salmonella along with qualitative microflora are also reported. The bacterial counts of water rangedfrom 5 x 102/gto 8.8 x 103/g whereas that of shrimp rangedfrom 2.0 x IO"/g to 9.0 x lO'/g. E. coli. ranged from 3 to II/g for prawns 3/I00ml. to 49/I00ml. for pond water. Two shrimp samples were positive for v. parahaemolyticus bacterial counts, coliforms or E. coli counts did not show any correlation with water salinity, which rangedfrom 14-18 ppt, Gram positive bacteria were predominant in shrimp and were represented by Micrococci (41.8%). Corynebacterium (19.3%) and Bacillus (14.2%). Common gram-negatives were Vibrios (19.2%) and Pseudomonas (5%).
Keywords: Pathogenic organisms; Cultured shrimp; Penaeus monodon